Pulse profile modelling of the accretion-powered millisecond pulsar SAX J1808.4−3658 using NICER data from its 2019 and 2022 outbursts - Dorsman, Bas; Salmi, Tuomo; Watts, Anna L.; Ng, Mason; Bobrikova, Anna; Loktev, Vladislav; Poutanen, Juri; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2026)
Pulse profile modelling is a relativistic ray-tracing technique that has provided constraints on parameters, with a focus on mass and radius, of five rotation-powered millisecond pulsars. While the technique can also be applied to accretion-powered millisecond pulsars (AMPs), this requires accounting for the X-rays from the accretion disc and has only been applied to archival data from the Rossi X-ray Timing Explorer. Here, we apply a previously developed neutron star and accretion disc model to the NICER (Neutron star Interior Composition Explorer) data of the 2019 and 2022 outbursts of SAX J1808.4–3658. We find that a single circular hotspot model is insufficient to explain the data. Modelling with two hotspots and an accretion disc model provides better phase-residuals, but a spectral residual at around 1 keV remains. In contrast, we find a good fit with a flexible background approach, replacing the accretion disc. However, the inferred parameters are not robust due to a degeneracy in the origin of the non-pulsed radiation, which can be caused either by the background or a hotspot that is at least partially in view throughout a full rotation. This work represents an important next step in pulse profile modelling of AMPs by analysing NICER data and underlines the need for more accurate accretion disc and hotspot modelling to achieve robust parameter constraints. We expect the inclusion of higher energy and polarimetric data will provide complementary constraints on inclination, hotspot colatitude, and hotspot size, improving the accuracy of pulse profile modelling of AMPs.
CRIS-Team Scopus Importer:2026-01-02
Keywords: accretion; accretion discs; equation of state; stars: individual: SAX J1808.4–3658; stars: neutron; X-rays: binaries